Empirically Based Play Interventions for Children - Reddy, Linda A., Ed; Files-Hall, Tara M., Ed; Schaefer, Charles E., Ed (APA Books, 2005)
"Empirically Based Play Interventions for Children" is a compilation of innovative, well-designed play interventions, presented for the first time in one text. Play therapy is the oldest and most popular form of child therapy in clinical practice and is widely considered by practitioners to be uniquely responsive to children's developmental needs. Play promotes normal child development and can help alleviate emotional and behavioral difficulties. Even so, play-based interventions have often been criticized for the lack of an empirical base to prove their efficacy. In an era of cost-containment, the need to provide evidence of the effectiveness of interventions is increasingly important in order to gain the general acceptance of third-party payers, mental health professionals, and consumers. This book answers the call from professional and managed-care organizations for research-based treatment methods with proven efficacy. It describes a range of play interventions that feature flexibility in service delivery and across settings, child populations and age groups. The editors and their contributors detail vital treatment components, including interventions that accommodate the developmental level of the child, target functional behaviors and competencies in children and parents, use psychometrically sound and clinically sensitive outcome assessments, and define successful outcomes by statistically meaningful methods. Clinicians and researchers alike will benefit from this landmark text and will gain a fuller understanding of the key ingredients for developing future play interventions. This book begins with a foreword: (1) Announcing Empirically Based Play Interventions for Children (Linda A. Reddy, Tara M. Files-Hall, and Charles E. Schaefer). Part I, Empirically Based Play Prevention Programs, contains: (2) The Primary Mental Health Project: A Play Intervention for School-Age Children (Deborah B. Johnson, JoAnne L. Pedro-Carroll, and Stephen P. Demanchick); (3) Intensive Play Therapy With Child Witnesses of Domestic Violence (Sarina Kot and Ashley Tyndall-Lind); and (4) A Preventive Play Intervention to Foster Children's Resilience in the Aftermath of Divorce (JoAnne L. Pedro-Carroll and Sheryl H. Jones). Part II, Empirically Based Play Interventions for Internalizing Disorders, contains: (5) Posttraumatic Play Therapy: The Need for an Integrated Model of Directive and Nondirective Approaches (Janine S. Shelby and Erika D. Felix); (6) Guided Fantasy Play for Chronically Ill Children: A Critical Review (Melissa R. Johnson and Jennifer L. Kreimer); and (7) A Review of Play Interventions for Hospitalized Children (William A. Rae and Jeremy R. Sullivan). Part III, Empirically Based Play Interventions for Externalizing Disorders, contains: (8) Child ADHD Multimodal Program: An Empirically Supported Intervention for Young Children With ADHD (Linda A. Reddy, Craig Springer, Tara M. Files-Hall, Elizabeth Schmelzer Benisz, Yvonne Hauch, Dania Braunstein, and Tanya Atamanoff); (9) Parent-Child Interaction Therapy for Children Experiencing Externalizing Behavior Problems (Amy D. Herschell and Cheryl B. McNeil); and (10) A Cooperative Games Intervention for Aggressive Preschool Children (April K. Bay-Hinitz and Ginger R. Wilson). Part IV, Empirically Based Play Interventions for Developmental Disorders and Related Issues, contains: (11) Play Interventions for Young Children With Autism Spectrum Disorders (Sally J. Rogers); and (12) Filial Therapy: A Critical Review (Rise VanFleet, Scott D. Ryan, and Shelly K. Smith). Part V, Final Comments, contains (13) Present Status and Future Directions for Empirically Based Play Interventions for Children (Tara M. Files-Hall and Linda A. Reddy). An author index and a subject index are included.